Revisiting indigenous education - Hughes, Helen, 1928-2013.; Hughes, Mark, 1957-; Centre for Independent Studies (Australia) (St Leonards, N.S.W. : The Centre for Independent Studies, 2009)
"Summarises the 2008 NAPLAN [National Assessment Program - Literacy and Numeracy] results that show that while South Australia, Western Australia, and Queensland have remote Indigenous education programs, in the Northern Territory Indigenous education is in crisis." - page 2.
Includes bibliographical references.
Also available on the Internet. Address as of 12/6/2009: http://www.cis.org.au/policy_monographs/pm94.pdf
Keywords: Children, Aboriginal Australian -- Education; Literacy -- Australia -- Statistics; Numeracy -- Australia -- Statistics; Education - Achievement; Education - Schools - Attendance; Education - Skills and curriculum - Numeracy and mathematics; Education - Secondary; Education - Primary; Education - Language - Literacy; Australia